2004
DOI: 10.1111/j.1475-2743.2004.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Can tree shelterbelts on agricultural land reduce flood risk?

Abstract: Abstract. Agricultural practices in the UK have come under increased scrutiny since the heavy and widespread flooding of 2000 and 2001. Although the impact of land use on runoff and flood risk is of growing concern, there are few quantitative data available. A preliminary study was undertaken in the Nant Pontbren catchment, mid‐Wales. Experimental tree shelterbelts were established in selected pastures of land used for sheep grazing. Water infiltration rates were up to 60 times higher in areas planted with yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 10 publications
4
38
0
2
Order By: Relevance
“…Soil compaction from plows and heavy machinery, loss of vegetative cover, and rapid drainage off properties are all linked to increased surface run‐off and potential flood losses (O'Connell et al ., ; Wheater and Evans, ). In particular, reduction in soil infiltration rates and water storage capacity can significantly increase overland flow into adjacent areas (Carroll et al ., ). However, not all agricultural operations are the same.…”
Section: The Role Of Location In Predicting Flood Lossesmentioning
confidence: 97%
“…Soil compaction from plows and heavy machinery, loss of vegetative cover, and rapid drainage off properties are all linked to increased surface run‐off and potential flood losses (O'Connell et al ., ; Wheater and Evans, ). In particular, reduction in soil infiltration rates and water storage capacity can significantly increase overland flow into adjacent areas (Carroll et al ., ). However, not all agricultural operations are the same.…”
Section: The Role Of Location In Predicting Flood Lossesmentioning
confidence: 97%
“…To address this research gap, an experimental programme was undertaken between 2004 and 2012 at Pontbren in Wales (Figure ) as part of a UK flood risk management research programme (Pender, ; Marshall et al ., ). Building upon preliminary studies that showed how destocking and tree planting can significantly improve infiltration rates (Carroll et al , ), a component of the Pontbren experiment has been to establish small‐scale manipulation plots to investigate the hydrological effects of destocking and native broadleaf tree planting under controlled conditions, and the variability of effects over space and time. In this paper, the results from the plot scale experiments are discussed in the context of previous research aiming to provide new insights into the effects of upland land management change on runoff processes, particularly in relation to climatic variability.…”
Section: Introductionmentioning
confidence: 97%
“…Conversely, the removal of livestock is generally observed to lead to a reduction in surface flow volumes that is attributed to an improvement in the structure of the upper layers of the soil, enhanced infiltration, and evaporation (e.g. Gifford and Hawkins, ; Greenwood et al ., ; Nguyen et al ., ; Greenwood and McKenzie, ; Carroll et al ., ; Carroll et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They have also noted that ‘shelter belts’– small strips of land planted with trees for the purpose of providing shelter to livestock – have mitigated the increase in runoff rates. A preliminary study, examining the impacts of tree plantations on soil at the Pontbren farms, indicated that strategically placed, small‐scale planting of trees for shelter can be used to improve the infiltration capacity of grazed permanent pasture (Carroll et al , 2004). Following this, an intensive experimental programme was initiated under the FRMRC to further examine how changes in land use might impact at different spatial scales – plot scale, field scale and catchment scales.…”
Section: Site Description and Overview Of Experimental And Modelling mentioning
confidence: 99%